Radiofrequency and microwave ablation in combination with transarterial chemoembolization induce equivalent histopathologic coagulation necrosis in hepatocellular carcinoma patients bridged to liver transplantation - Vasnani, Raj (Hepatobiliary Surg Nutr, 2016)
BACKGROUND: Bridging therapy plays an increasingly important role in the management of patients with hepatocellular carcinoma (HCC) awaiting liver transplantation (LT). Combination therapy with drug-eluting bead transarterial chemoembolization (DEB-TACE) and percutaneous thermal ablation, such as radiofrequency ablation (RFA) or microwave ablation (MWA), has shown success at prolonging survival and bridging patients to LT. However, few studies have evaluated the two combination therapy regimens head-to-head at a single institution, and fewer have compared histopathology. This retrospective study compares tumor coagulation on explanted livers in patients with HCC treated with DEB-TACE sequentially combined with RFA versus MWA. METHODS: From 2005 to 2015, 42 sequential patients underwent combination therapy prior to LT by Milan criteria, with 11 patients (11 tumors; mean, 2.9 cm; range, 1.8–4.3 cm) in the DEB-TACE/RFA cohort and 31 patients (40 tumors; mean, 2.4 cm; range, 1.1–5.4 cm) in the DEB-TACE/MWA cohort. The mean TACE procedures in the RFA and MWA cohorts were 1.3 (range, 1–2) and 1.3 (range, 1–3), respectively. The mean thermal ablations in the RFA and MWA cohorts were 1.2 (range, 1–2) and 1.3 (range, 1–3), respectively. Tumor coagulation was evaluated on explanted livers. RESULTS: Mean tumor coagulation in the RFA and MWA cohorts were 88.9% (range, 0–100%) and 90.5% (range, 30–100%), respectively (P=0.82). Rates of complete tumor coagulation in the RFA and MWA cohorts were 45% and 53%, respectively (P=0.74). No difference in tumor coagulation was found between the cohorts when separating tumors <3 cm (P=0.21) and >3 cm (P=0.09). Among all 51 tumors, the 36 in complete response (CR) on imaging at LT demonstrated mean tumor coagulation of 95.8%. No correlation was found between tumor coagulation and initial tumor size or time interval to LT. No tumor seeding was seen along the ablation tracts. CONCLUSIONS: RFA and MWA in sequential combination with DEB-TACE, used as a bridge to LT, are equally efficacious at inducing HCC tumor coagulation.